STRATEGI PENGEMBANGAN SDM INDUSTRI KREATIF INDONESIA DALAM MENGHADAPI MASYAKARAT EKONOMI ASEAN PADA TAHUN 2016 - Hidayat, Agi Syarif; Nurdiana, Editya (Prosiding Seminar Nasional INDOCOMPAC)
The purpose of this study was to determine the development strategy of the Human Resources (HR) Indonesia's creative industries in the ASEAN Economic Community in 2016. The method used is a method of qualitative research, source of research data used documents, books and Internet data. The data used is secondary data. Data collection techniques used were document. Data analysis techniques used through the stages of data collection, data reduction, data display, and decision-making. Human resource development strategy of creative industry in Indonesia can be conducted by: 1) increasing the quality and quantity of creative educational institutions and 2) increasing the capacity of creative labor. Improving the quality and quantity of creative educational institutions marked by the increasing number of creative educational institutions, improving the quality of education of creative educational institutions as well as the increase of graduates from educational institutions were absorbed in the world of creative work. Increasing the capacity of creative labor is characterized by increasing creative labor force that has a globally-recognized certification as well as their system of labor protection for workers in the creative industry sector. Keywords: Human Resources, Industrial, Creative, AEC   Tujuan penelitian ini adalah untuk mengetahui strategi pengembangan Sumber Daya Manusia (SDM) industri kreatif Indonesia dalam menghadapi Masyarakat Ekonomi ASEAN pada tahun 2016.  Metode penelitian yang digunakan adalah metode penelitian kualitatif, sumber data penelitian menggunakan dokumen, buku dan data internet. Jenis data yang digunakan adalah data sekunder. Teknik pengumpulan data yang digunakan adalah dokumen. Teknik analisis data yang digunakan melalui tahap pengumpulan data, reduksi data, display data dan pengambilan keputusan. Strategi pengembangan SDM Industri kreatif di Indonesia dapat dilaksanakan dengan cara : 1) peningkatan kualitas dan kuantitas lembaga pendidikan kreatif serta 2) peningkatan kapasitas tenaga kerja kreatif.  Peningkatan kualitas dan kuantitas lembaga pendidikan kreatif ditandai dengan bertambahnya jumlah lembaga pendidikan kreatif, meningkatnya mutu pendidikan lembaga pendidikan kreatif serta meningkatnya lulusan dari lembaga pendidikan kreatif yang terserap didunia kerja. Peningkatan kapasitas tenaga kerja kreatif ditandai dengan meningkatnya tenaga kerja kreatif yang memiliki sertifikasi yang diakui secara global serta adanya adanya sistem perlindungan tenaga kerja bagi tenaga kerja di sektor Industri kreatif. Kata Kunci : SDM, Industri, Kreatif, MEA.